Nonverbal and Verbal Signs in the Music Video Forever Young by Alphaville (1984) - I Made Duari Kurnia Radhika; Novita Mulyana; Ketut Santi Indriani (Pusat riset dan Inovasi Nasional, 2025)
This study is titled Nonverbal and Verbal Signs in the Music Video Forever Young by Alphaville (1984). It examines how verbal and nonverbal signs in the music video are used to represent messages about youth, time, and emotional longing through a semiotic approach. The objectives of this study are to identify the verbal and nonverbal signs used in the video and to analyze how these signs construct symbolic emotional, cultural, and philosophical meanings. The data consists of visual scenes and lyrics from the official “Forever Young” music video. Data collection was conducted through observation by listening to the song, reading the lyrics, and documenting the visuals. The analysis employs a qualitative descriptive method, applying relevant theories of meaning, visual semiotics, and color symbolism. The findings show that the music video uses a combination of affective, connotative, and conceptual meanings to convey its message. The most dominant nonverbal aspects are props, manner, and activity, while appearance and content analysis are also present with less frequency. In the verbal signs, affective and connotative meanings appear most often, reflecting strong emotional nuance and symbolic references to youth and existential reflection.